On the modelling of infilled RC frames through strut models. Issue 1 (1st January 2017) - Tanganelli, Marco; Rotunno, Tommaso; Viti, Stefania
Abstract: Infill panels largely affect the seismic response of framed constructions. The wide variety in their mechanical and geometrical features has produced many different models and assumptions in their analytical representation. In this paper the simplest and most diffuse analytical approach, based on the introduction of equivalent struts, has been checked. An overview is presented, focusing on the strut dimensions, strength and number. Two case-studies, taken by two different experimental campaigns, have been considered and reproduced. The obtained results have been compared to the experimental ones, and some parameters have been checked for selecting the model to use for analysis.